Succession Planning for Organisational Survival: Challenges and Recommendations - Muhamad Azmi, Muhamad ‘Abdin Syakirin; Ibrahim, Muhammad Alif Asyraf; Mohd Shukor, Muhammad Shukry Hakimi; Abdul Rahim, Abdul Amir Ikhwan; Puteh, Fadilah; Ahmad Kamal, Alia Nadhirah (UUM Press, 2025)
Succession planning is an important component of organisational strategy because it assures leadership continuity and preserves institutional knowledge. In an era of fast change and unpredictability, an organisation's capacity to plan for and manage leadership changes is critical to its long-term survival and success. This study discusses the issues of succession planning and provides advice for overcoming them to ensure organisational resilience. This paper employs a scoping review conducted to investigate the existing literature on challenges and recommendations in succession planning for organisational survival in the era of Volatility, Uncertainty, Complexity, and Ambiguity (VUCA) so that organisations can prepare to deal with human capital in the VUCA world effectively. The process of gathering data for this scoping review involves looking up articles on Google Scholar, web of science and Scopus through which 15 articles have been identified to be relevant. The challenges of succession planning are then explored in detail, including the talent development and retention, cultural and generational differences and resistance to change and institutionalisation. Overall, this study provides a comprehensive analysis of the challenges and opportunities associated with succession planning, along with practical recommendations for organisations’ effective succession strategies which promote their strategic goals and enhance their resilience in the face of change